The Influence of Company Size, Institutional Ownership, and Profitability on Dividend Policy in Manufacturing Companies - Dwiyanti, Annisa; Lawita, Florencia Irena; Adrian, Michael (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Dividend policy is important thing for companies because it can be reference for investors in making decisions to invest. This research aims to examine the effect of firm size, instiutional ownership, and profitability on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. This research uses a quantitative approach with a sample size of 28 manufacturing companies. The data used consists of secondary data from companies annual financial statemens. The analysis used is multiple regression analysis with data processing using SPSS 27. The result show that firm size has no effect on the dividend policy, while institutional ownership and profitability have an effect on dividend policy.